Spiritual Resilience in Multicultural Schools: Tahfidz High School Students' Efforts in Maintaining Qur’an Memorisation - Andhika Sugeng Riyanto; M. Rikza Chamami; Fihris Fihris (Yayasan Letiges Konsultan Sosial, 2026)
This study was motivated by the development of the Tahfidz Qur'an programme in public schools and the limited research on the spiritual resilience of tahfidz students in public secondary schools that are multicultural in terms of religion and social background. This study aims to analyse the commitment, challenges, and adaptive strategies of tahfidz students in maintaining their memorisation of the Qur'an at SMA Negeri 3 Semarang. The research used a qualitative approach with a case study design. Data collection techniques included unstructured interviews, non-participatory observation, and documentation, with primary data sources in the form of interviews and observations, and secondary data sources in the form of supporting documents for the tahfidz programme. Data analysis was carried out using the Miles and Huberman model, while data validity was maintained through triangulation and member checking techniques. The results of the study show that the Tahfidz Programme at SMA Negeri 3 Semarang was born from the initiative of parents, supported by the school, PPPA (Program Pelatihan Penghafal Al-Qur’an) Darul Qur'an, and alums. Commitment to memorisation was formed through religious socialisation and intrinsic motivation. Multicultural challenges were relatively minor, in the form of awkwardness and peer distraction. Students applied social adaptation and self-regulation to maintain consistent and continuous muraja'ah.